Conduction mechanisms in a planar nanocomposite resistive switching device based on cluster-assembled Au/ZrOx films - Cipollini, Davide; Profumo, Filippo; Schomaker, Lambert; Milani, Paolo; Borghi, Francesca (Frontiers in Materials, 2024)
Nanostructured zirconia and gold films (ns-Au/ZrOx) have been demonstrated as devices characterized by non-linear and hysteretic electrical behavior, with short-term memory and potentiation/depression activity. Here we investigate the conduction mechanisms regulating the non-linear behavior of the nanostructured bilayer Au/ZrOx films. In particular, we investigated the hysteretic I-V curves following the Chua's approach to memristive systems and separately modelling ion migration and electron transport in the films. The conduction mechanisms exhibited by the bilayered nanostructured system are strongly influenced by the nanogranular morphology that dynamically changes because of electrical stimuli; structural rearrangements are particularly promoted by intense local electric fields and high mobility along bottlenecks and edges in the microstructure. Electron transport is accounted for the Schottky barrier at the electrode interfaces and Poole-Frankel effect in the bulk nanogranular material, according to a dynamic reorganization of the cluster-assembled network. A model for Poole-Frankel effect is here discussed to include saturation of the Coulombic traps in the high applied field regime; the proposed model has been validated with experimental voltage ramps with varying sweep-velocity and at different temperatures (from 300 to 200 K), as also by a power exponent parameter analysis.